Effects of Cigarette Smoke on the Nasal Respiratory and Olfactory Mucosa in Allergic Rhinitis Mice - Ueha, Rumi; Ueha, Satoshi; Kondo, Kenji; Nishijima, Hironobu; Yamasoba, Tatsuya (Frontiers in Neuroscience, 2020)
Objective: Cigarette smoke (CS) exposure reportedly enhances allergic airway inflammation. However, some studies have shown an association between current cigarette smoke exposure and a low risk for allergic rhinitis. Thus, the impact of CS exposure on allergic rhinitis remains poorly understood. The purpose of this study was to investigate the effects of CS on the respiratory mucosa (RM) and the olfactory epithelium (OE) of mice with allergic rhinitis, as the effects may differ depending on the nasal histological compartments. Methods: Eight-week-old male BALB/c mice were used for this study. We developed a mouse model of smoking by intranasally administering 10 doses of a CS solution (CSS), and a mouse model of allergic rhinitis by sensitization with intraperitoneal ovalbumin (OVA) injection and intranasal challenge with OVA. We examined the effects of CS on the nasal RM and OE in mice with or without allergic rhinitis using histological, serum, and genetic analyses. First, we examine whether CSS exposure induces allergic responses and then, examined allergic responses in the OVA-sensitized allergic rhinitis mice with or without CSS exposure. Results: Short-term CSS administration intensified allergic responses including increased infiltration of eosinophils and inflammatory cells and upregulation of interleukin-5 expression in the nasal RM of OVA-immunized mice, although only CSS induced neither allergic responses nor impairment of the RM and OE. Notably, repetitive OVA-immunization partially impaired the OE in the upper-lateral area, but CSS administration did not reinforce this impairment in OVA-induced allergic mice. Conclusion: Short-term CSS exposure strengthened allergic responses in the nasal RM and did not change the structure of the OE. These results suggest that patients with allergic rhinitis could experience exacerbation of allergic symptoms after CS exposure.